A method for preparing dust-free acid-resistant graphite boat
The chemical crosslinking of the titanate coupling agent and the surface of the graphite boat is formed to form a TiC/TiO2 coating, which solves the problems of pulverization and short service life of the graphite boat, and realizes a dust-free and acid-resistant graphite boat, which is suitable for PECVD process in high temperature and acid environments.
Patent Information
- Application Number
- CN202411604418.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The performance of existing graphite boats will decline after long-term use and will easily become powdered, resulting in a decrease in coating efficiency and product quality.
The titanate coupling agent is used to chemically cross-link with the surface of the graphite boat to form a TiC/TiO2 coating, and a dust-free and acid-resistant graphite boat is formed by high-temperature calcination treatment.
Effectively prevent graphite boat powdering, improve service life, ensure coating efficiency and product quality, and is suitable for PECVD processes in high temperature and acidic environments.
Smart Images

Figure CN119118708B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a manufacturing technology of semiconductor device production equipment, and in particular to a preparation technology of a graphite boat used for carrying materials such as silicon wafers in a photovoltaic PECVD coating process. Background Art
[0002] Graphite boats are essential in the PECVD coating process for semiconductors and photovoltaics. They are used as carriers to deposit thin films on silicon wafers, a key step in the manufacture of solar cells and other semiconductor devices. This graphite material can withstand high temperatures and chemical corrosion, ensuring the stability of the production process and the high quality of the product.
[0003] At present, the development of PECVD graphite boats is focusing on improving their durability and reducing production costs. With the growing demand for renewable energy, the photovoltaic industry has an increasing demand for efficient and long-life graphite boats. Graphite is a good conductor of heat and electricity, with high electrical conductivity, chemical stability, thermal stability, corrosion resistance, low density and other advantages. It has inherent unique advantages in making graphite boats. However, because graphite is a porous and brittle material, and because of the interaction between the layers of the graphite material, the van der Waals force interaction between the layers will cause the phenomenon of ash falling (delamination). In addition, amorphous silicon will gradually be deposited on the graphite boat during the PECVD coating process. If it is not removed in time, it will affect the effect of the amorphous silicon film, resulting in uneven coating, film explosion and film stripping on the surface of the silicon wafer and the boat wall, and a decrease in the coating rate, and even the situation where the coating cannot continue. Therefore, the industry usually chooses to use hydrofluoric acid (such as CN103521473A) and hydrofluoric acid + hydrogen peroxide (such as CN106952805A) for immersion treatment. However, after being soaked and cleaned in hydrofluoric acid, the graphite boat is prone to powdering. The above factors combined lead to the following practical problems: (1) The service life of the graphite boat is shortened: the performance of the graphite boat decreases after long-term use, and the first boat coating efficiency is lower than the production line efficiency due to the powdering problem; (2) In the PECVD process, the powdering of the graphite boat will leave marks on the silicon wafer after being stored for too long, affecting product quality.
[0004] Therefore, it is urgent to develop a new graphite boat preparation technology to solve the above problems. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a dust-free, acid-resistant graphite boat.
[0006] To solve the technical problem, the solution of the present invention is:
[0007] Provided is a method for preparing a dust-free, acid-resistant graphite boat, comprising the following steps:
[0008] (1) Process the isostatically pressed graphite into a graphite boat, wash it with deionized water and set it aside;
[0009] (2) Add a titanate coupling agent to ethanol with a purity of 95%, with the volume mass ratio of ethanol to titanate coupling agent being 100-500 L: 10-50 kg; after mixing evenly, add acid solution to adjust the pH value to 1-5.5; continue stirring at 25-85°C for 2-8 h to hydrolyze the titanate coupling agent to obtain a modified solution;
[0010] (3) Immerse the graphite boat in the modified solution at room temperature and pressure for 5 to 96 hours;
[0011] (4) Take out the graphite boat, wash it with water and ethanol, and then dry it;
[0012] (5) The graphite boat is burned under vacuum or inert atmosphere to obtain a dust-free and acid-resistant graphite boat.
[0013] As a preferred embodiment of the present invention, in the step (1), a CNC engraving machine is used to machine the isostatic graphite to obtain a graphite boat.
[0014] As a preferred embodiment of the present invention, the titanate coupling agent in step (2) is any one of di(acetylacetonate)titanate diisopropyl ester, bis(triethanolamine)titanate diisopropyl ester, isopropoxy tri(dodecylbenzenesulfonyloxy)titanate, or a mixture of two or more thereof.
[0015] As a preferred embodiment of the present invention, the acid in step (2) is any one of glacial acetic acid, hydrochloric acid, sulfuric acid or citric acid.
[0016] As a preferred embodiment of the present invention, the washing in step (4) refers to washing with water for 1 to 5 times and then washing with ethanol for 1 to 3 times.
[0017] As a preferred embodiment of the present invention, the drying in step (4) refers to placing the cleaned graphite boat into an oven and treating it at 50-200° C. for 2-15 h.
[0018] As a preferred embodiment of the present invention, in step (5), the graphite boat is first moved to a high-temperature sintering furnace; then the pressure in the furnace is made to be 2×10 -7 kPa, or introduce inert gas into the furnace to make the pressure in the furnace 3 ~ 60kPa; under this condition, the burning treatment is carried out.
[0019] As a preferred embodiment of the present invention, the inert gas is nitrogen or argon.
[0020] As a preferred embodiment of the present invention, the calcination in step (5) refers to first raising the temperature to 500-1100°C at a rate of 0.3-10°C / min, keeping the temperature for 0.5-6h, and then naturally cooling the temperature to room temperature.
[0021] Description of the invention principle:
[0022] The technical implementation process of the present invention includes the following contents:
[0023] Graphite boat machining: The present invention uses isostatic graphite as the base material for preparing the graphite boat, and through machining, it is made into a graphite boat shape suitable for the PECVD process. Isostatic graphite has a high density and uniformity, which provides a good foundation for the uniform deposition of subsequent coatings.
[0024] Preparation of coupling agent solution: Dissolve the titanate coupling agent in 95% ethanol to form a solution. The titanate coupling agent is used to enhance the bonding between the substrate and the coating. By adding acid to adjust the pH value of the solution to 1-5.5, it is helpful for the hydrolysis and polymerization of the coupling agent and makes it easier to react with the graphite surface.
[0025] Solution heating and activation: The mixed solution containing the coupling agent is heated and stirred. This operation is conducive to the further hydrolysis and polymerization of the coupling agent to form oligomers, and to the formation of a coating with sufficient adhesion on the graphite surface in the subsequent steps.
[0026] Graphite boat surface modification: Soak the cleaned graphite boat in the modification solution. This step allows the graphite boat surface to fully react with the coupling agent, that is, the titanium hydroxyl generated by the hydrolysis of titanate reacts with the hydroxyl on the graphite material to condense, so that the titanate molecules and the graphite floor material are chemically cross-linked (covalently bonded) to complete the surface modification. At the same time, because it is chemically cross-linked, the adhesion between the titanate molecules and the graphite substrate is very good, which can inhibit the powdering effect on the product surface.
[0027] Cleaning and drying: The modified graphite boat is washed with water and ethanol for many times to remove the unreacted coupling agent and other impurities. The cleaned graphite boat is dried in an oven to ensure that its surface is dry, so that the titanium-based coupling agent polymer is dehydrated to form a cross-linked coating attached to the surface of the graphite boat.
[0028] Deposition of titanium-based coating: The dried graphite boat is subjected to high-temperature calcination and heat preservation treatment under vacuum conditions. In this step, further chemical reactions occur on the surface of the graphite boat, and the titanium-based material is deposited at high temperatures to form a TiC / TiO2 coating. Controlling the heating rate can ensure the uniformity and quality of the coating, and achieve the purpose of dust-free (preventing the graphite boat from powdering), acid resistance, and preventing boat marks.
[0029] Compared with the prior art, the technical effects of the present invention are:
[0030] 1. The main coating material used in the present invention is a titanate coupling agent; under acidic conditions and the action of trace water (water contained in 95% ethanol), the titanate coupling agent is hydrolyzed and can be closely combined with the graphite material to form a chemical crosslink; further, a TiC / TiO2 coating is formed under high temperature deposition to achieve dust-free protection of the surface of the graphite boat.
[0031] 2. In the present invention, the porous characteristics of the graphite material are utilized by impregnation at normal pressure, and the titanate coupling agent solution is allowed to spontaneously enter the graphite material through the capillary principle. This process realizes energy-free impregnation at normal temperature and pressure, greatly reducing the production cost.
[0032] 3. The main material used in the present invention is isostatic graphite, which has many excellent properties, is a good conductor of heat and electricity, has the advantages of high conductivity, chemical stability, thermal stability, corrosion resistance, low density, etc. By using it with commercial titanate coupling agents, graphite powderization can be prevented and the service life of graphite boat products can be increased.
[0033] 4. The method of the present invention is simple to operate, has low equipment requirements, and has low comprehensive costs. The obtained dust-free acid-resistant graphite boat has good use effect in actual production operation. The graphite boat processing process does not increase the mechanical processing cost, and can greatly extend the service life and prevent problems such as boat marks. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention is a simplified flow chart for preparing the modified graphite boat. DETAILED DESCRIPTION
[0035] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.
[0036] The method for preparing the dust-free acid-resistant graphite boat of the present invention comprises the following steps:
[0037] (1) Use a CNC engraving machine to machine isostatic graphite to obtain a graphite boat; wash it with deionized water and set it aside;
[0038] (2) Add a titanate coupling agent to ethanol with a purity of 95%, with the volume mass ratio of ethanol to titanate coupling agent being 100-500 L: 10-50 kg; after mixing evenly, add acid solution to adjust the pH value to 1-5.5; continue stirring at 25-85°C for 2-8 h to hydrolyze the titanate coupling agent to obtain a modified solution;
[0039] The titanate coupling agent is any one of di(acetylacetonate)titanate diisopropyl, di(triethanolamine)titanate diisopropyl, isopropoxy tri(dodecylbenzenesulfonyloxy)titanate, or a mixture of two or more thereof. The acid is any one of glacial acetic acid, hydrochloric acid, sulfuric acid or citric acid;
[0040] (3) Immerse the graphite boat in the modified solution at room temperature and pressure for 5 to 96 hours;
[0041] (4) Take out the graphite boat, wash it with water and ethanol, and then dry it;
[0042] The cleaning refers to washing with water for 1 to 5 times and then washing with ethanol for 1 to 3 times; the drying refers to placing the cleaned graphite boat in an oven and treating it at 50 to 200° C. for 2 to 15 hours.
[0043] (5) Burn the graphite boat under vacuum or inert atmosphere to obtain a dust-free and acid-resistant graphite boat. Specifically, first move the graphite boat to a high-temperature sintering furnace; then use a vacuum pump to make the pressure in the furnace 2×10 -7 kPa, or introduce an inert gas into the furnace to make the pressure in the furnace 3 to 60 kPa; perform the burning treatment under this condition. The inert gas is nitrogen or argon. During the burning treatment, first increase the temperature to 500 to 1100°C at a rate of 0.3 to 10°C / min, keep the temperature for 0.5 to 6 hours, and then naturally cool to room temperature.
[0044] The 95% purity ethanol, titanate coupling agent and acid solution described in the present invention can all be commercially available products.
[0045] In the following embodiments and comparative examples, the graphite boats used are all made from the same batch of commercially available isostatic graphite products (model Wuxing-7).
[0046] Embodiment 1:
[0047] (1) Use a CNC engraving machine to process isostatic graphite into a graphite boat suitable for PECVD process; wash the floating dust with deionized water and set aside.
[0048] (2) Pour 10 kg of diisopropyl di(acetylacetonate)titanate into 100 L of 95% pure ethanol, and adjust the pH of the mixed solution to 1 using glacial acetic acid; stir the mixed solution and heat it at 25°C for 8 h to obtain a modified solution.
[0049] (3) Soak the graphite boat in the modified solution at room temperature and pressure for 5 h.
[0050] (4) Take out the graphite boat, wash it once with water and then three times with ethanol. Finally, put the washed graphite boat into an oven and dry it at 50℃ for 15 h.
[0051] (5) Move the graphite boat to a high-temperature vacuum sintering furnace, and then use a vacuum pump to make the pressure in the furnace 2×10 -7 kPa; then the temperature was raised to 500°C at a rate of 0.3°C / min, kept at that temperature for 6 hours and then naturally cooled to room temperature to obtain a modified dust-free, acid-resistant graphite boat.
[0052] Embodiment 2:
[0053] (1) Use a CNC engraving machine to process isostatic graphite into a graphite boat suitable for PECVD process; wash the floating dust with deionized water and set aside.
[0054] (2) Pour 26 kg of a mixture of diisopropyl di(acetylacetonate)titanate and diisopropyl di(triethanolamine)titanate (the mass ratio of the two is 1:1) into 300 L of 95% pure ethanol, and adjust the pH of the mixed solution to 3 with citric acid. Stir the mixed solution and heat it at 50°C for 4 h to obtain a modified solution.
[0055] (3) Soak the graphite boat in the modified solution at room temperature and pressure for 40 h.
[0056] (4) Take out the graphite boat, wash it twice with water and then twice with ethanol, and finally put the washed graphite boat plate into an oven and dry it at 200℃ for 2h.
[0057] (5) The graphite boat was moved to a high-temperature vacuum sintering furnace, and nitrogen was introduced into the furnace and maintained at 3 kPa. The temperature was then raised to 800 °C at a rate of 6 °C / min, and after being kept at that temperature for 1 h, the temperature was naturally lowered to room temperature to obtain a modified dust-free, acid-resistant graphite boat.
[0058] Embodiment 3:
[0059] (1) Use a CNC engraving machine to process isostatic graphite into a graphite boat suitable for PECVD process; wash the floating dust with deionized water and set aside.
[0060] (2) Pour 50 kg of a mixture of diisopropyl di(acetylacetonate)titanate, diisopropyl bis(triethanolamine)titanate, and isopropoxytri(dodecylbenzenesulfonyloxy)titanate (the mass ratio of the three is 1:1:1) into 500 L of 95% ethanol, and adjust the pH of the mixed solution to 5.5 with hydrochloric acid; stir the mixed solution and heat it at 85°C for 2 h to obtain a modified solution.
[0061] (3) Soak the graphite boat in the modified solution at room temperature and pressure for 96 h.
[0062] (4) Take out the graphite boat, wash it with water for 5 times and then with ethanol once, and finally put the washed graphite boat into an oven and dry it at 100℃ for 8 h.
[0063] (5) Take out the dried graphite boat, then introduce nitrogen into the furnace and maintain it at 10 kPa; then heat it to 1100°C at a rate of 10°C / min, keep it at that temperature for 2 h, and then naturally cool it to room temperature to obtain a modified dust-free, acid-resistant graphite boat.
[0064] Embodiment 4:
[0065] (1) Use a CNC engraving machine to process isostatic graphite into a graphite boat suitable for PECVD process; wash the floating dust with deionized water and set aside.
[0066] (2) Pour 15 kg of diisopropyl bis(triethanolamine)titanate into 200 L of 95% pure ethanol, and adjust the pH of the mixed solution to 2 with sulfuric acid; stir the mixed solution and heat it at 35°C for 6 h to obtain a modified solution.
[0067] (3) Soak the graphite boat in the modified solution at room temperature and pressure for 75 h.
[0068] (4) Take out the graphite boat, wash it with water for 4 times and then with ethanol for 2 times, and finally put the washed graphite boat into an oven and dry it at 75℃ for 10 hours.
[0069] (5) The graphite boat was moved to a high-temperature vacuum sintering furnace, and then argon gas was introduced into the furnace and maintained at 10 kPa; the temperature was then raised to 650°C at a rate of 1°C / min, and after being kept at that temperature for 4 h, the temperature was naturally cooled to room temperature to obtain a modified dust-free, acid-resistant graphite boat.
[0070] Example 5
[0071] (1) Use a CNC engraving machine to process isostatic graphite into a graphite boat suitable for PECVD process; wash the floating dust with deionized water and set aside.
[0072] (2) Pour 34 kg of isopropoxy tri(dodecylbenzenesulfonyloxy) titanate into 400 L of 95% pure ethanol, and adjust the pH of the mixed solution to 4 with citric acid; stir the mixed solution and heat it at 70°C for 3 h to obtain a modified solution.
[0073] (3) Soak the graphite boat in the modified solution at room temperature and pressure for 20 h.
[0074] (4) Take out the graphite boat, wash it twice with water and then three times with ethanol, and finally put the washed graphite boat into an oven and dry it at 150℃ for 6 h.
[0075] (5) The graphite boat was moved to a high-temperature vacuum sintering furnace, and nitrogen was introduced into the furnace and maintained at 40 kPa; the temperature was then raised to 950 °C at a rate of 8 °C / min, and after being kept at that temperature for 0.5 h, the temperature was naturally cooled to room temperature to obtain a modified dust-free, acid-resistant graphite boat.
[0076] Embodiment 6:
[0077] (1) Use a CNC engraving machine to process isostatic graphite into a graphite boat suitable for PECVD process; wash the floating dust with deionized water and set aside.
[0078] (2) Pour 26 kg of a mixture of diisopropyl di(acetylacetonate)titanate and isopropoxytri(dodecylbenzenesulfonyloxy)titanate (the mass ratio of the two is 1:1) into 300 L of 95% pure ethanol, and adjust the pH of the mixed solution to 3 with citric acid. Stir the mixed solution and heat it at 50°C for 4 h to obtain a modified solution.
[0079] (3) Soak the graphite boat in the modified solution at room temperature and pressure for 38 h.
[0080] (4) Take out the graphite boat, wash it twice with water and then three times with ethanol, and finally put the washed graphite boat plate into an oven and dry it at 200℃ for 2.5h.
[0081] (5) The graphite boat was moved to a high-temperature vacuum sintering furnace, and then argon gas was introduced into the furnace and maintained at 40 kPa; the temperature was then raised to 1100°C at a rate of 10°C / min, and after being kept at that temperature for 0.6 h, the temperature was naturally cooled to room temperature to obtain a modified dust-free, acid-resistant graphite boat.
[0082] Embodiment 7:
[0083] (1) Use a CNC engraving machine to process isostatic graphite into a graphite boat suitable for PECVD process; wash the floating dust with deionized water and set aside.
[0084] (2) Pour 26 kg of a mixture of diisopropyl bis(triethanolamine)titanate and isopropoxytri(dodecylbenzenesulfonyloxy)titanate (the mass ratio of the two is 1:1) into 300 L of 95% pure ethanol, and adjust the pH of the mixed solution to 3 with citric acid. Stir the mixed solution and heat it at 50°C for 4 h to obtain a modified solution.
[0085] (3) Soak the graphite boat in the modified solution at room temperature and pressure for 40 h.
[0086] (4) Take out the graphite boat, wash it twice with water and then twice with ethanol, and finally put the washed graphite boat plate into an oven and dry it at 200℃ for 2h.
[0087] (5) The graphite boat was moved to a high-temperature vacuum sintering furnace, and then argon gas was introduced into the furnace and maintained at 60 kPa; the temperature was then raised to 800 °C at a rate of 10 °C / min, and after being kept at this temperature for 1 h, the temperature was naturally lowered to room temperature to obtain a modified dust-free, acid-resistant graphite boat.
[0088] Comparative Example 1
[0089] The isostatically pressed graphite is processed into a graphite boat suitable for the PECVD process by machining; the unmodified graphite boat product is used as a comparative example.
[0090] Product testing and result analysis:
[0091] 1. Dust drop test of the product of the present invention
[0092] a. During the product modification operation of Examples 1-7 of the present invention, the graphite boat was taken out after step (4) and step (5) respectively to test its dust removal;
[0093] b. Place the modified dust-free acid-resistant graphite boat in a high-temperature vacuum sintering furnace, set the vacuum degree below 3 Pa, heat to 600 ° C and calcine for 45 minutes, then cool naturally to room temperature; test its ash loss;
[0094] c. Soak the modified dust-free acid-resistant graphite boat in a HF solution with a mass concentration of 11% for 18 hours, take it out, clean it, dry it, and then test its dust removal;
[0095] d. Repeat steps b and c for 5 times, and then test the dust removal condition.
[0096] The specific operation of the dust removal test is: stick the transparent tape on the surface of the graphite boat sample, and use the weight-bearing method to apply a load of 1kg to the surface for 60s; then remove the load, slowly tear off the transparent tape, and observe whether there is graphite powder on the transparent tape.
[0097] It has been verified that in each product prepared in Examples 1-7 of the present invention, no graphite powder sticking was found in each test operation a, b, c, and d, proving that the treatment of the coating by the modified product of the present invention is successful.
[0098] 2. Dust drop test of existing technology products
[0099] Take the product of comparative example 1, and cycle it 5 times according to the operations of steps b and c above, and then test its dust removal.
[0100] The test shows that the product of comparative example 1 has serious dusting after high temperature and acid leaching cycle treatment, and graphite powder is adhered to almost all the adhesive parts of the transparent tape. Combined with the actual application of the existing technology products in the PECVD process production line, it can be seen that the unmodified products are indeed difficult to meet the high-intensity production requirements.
[0101] 3. Practical application test of the product of the present invention
[0102] The dust-free, acid-resistant graphite boats prepared in Examples 1-7 of the present invention were used in the PECVD process production line of a certain enterprise in Zhejiang Province to conduct production tests under actual application conditions.
[0103] The statistical results after the test are as follows:
[0104] The first boat efficiency of the product in Example 1 is 0.19% higher than that of the traditional graphite boat; under PECVD coating conditions, it can be used normally for 5000 times;
[0105] The first boat efficiency of the product in Example 2 is 0.15% higher than that of the traditional graphite boat; under PECVD coating conditions, it can be used normally for 5500 times;
[0106] The first boat efficiency of the product in Example 3 is 0.17% higher than that of the traditional graphite boat; under PECVD coating conditions, it is normally used 6300 times;
[0107] The first boat efficiency of the product in Example 4 is 0.10% higher than that of the traditional graphite boat; under PECVD coating conditions, it can be used normally for 5000 times;
[0108] The first boat efficiency of the product in Example 5 is 0.11% higher than that of the traditional graphite boat; under PECVD coating conditions, it is normally used 5600 times;
[0109] The first boat efficiency of the product in Example 6 is 0.14% higher than that of the traditional graphite boat; under PECVD coating conditions, it can be used normally for 5500 times;
[0110] The first boat efficiency of the product in Example 7 is 0.15% higher than that of the traditional graphite boat; under PECVD coating conditions, it can be normally used 5500 times.
[0111] During the actual production and application of the products of the above embodiments 1-7, no abnormal conditions such as decreased efficiency during the first boat coating due to powdering of the graphite boat, or marks generated during storage of silicon wafers occurred. The used graphite boat was retested for dust loss using the aforementioned transparent tape sticking method, and no graphite powder sticking occurred. From the testing and verification experiments of the above products, it can be seen that the modified dust-free and acid-resistant graphite boat of the present invention still has the specific property of not shedding powder after multiple high-temperature burning and strong acid immersion treatments. Therefore, the product can be used under high-temperature conditions under PECVD coating conditions, as well as in the scenario of pickling and removing deposited amorphous silicon after use.
[0112] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a dust-free acid-resistant graphite boat, characterized in that: The following steps are involved: (1) Process the isostatically pressed graphite into a graphite boat, wash it with deionized water and set it aside; (2) Add a titanate coupling agent to ethanol with a purity of 95%, wherein the volume mass ratio of ethanol to titanate coupling agent is 100-500 L: 10-50 kg; after mixing evenly, add acid solution to adjust the pH value to 1-5.5; continue stirring at 25-85°C for 2-8 hours to hydrolyze the titanate coupling agent to obtain a modified solution; the titanate coupling agent is any one of di(acetylacetonate)titanate diisopropyl ester, bis(triethanolamine)titanate diisopropyl ester, isopropoxy tri(dodecylbenzenesulfonyloxy)titanate, or a mixture of two or more thereof; (3) Immerse the graphite boat in the modified solution at room temperature and pressure for 5 to 96 hours; (4) Take out the graphite boat, wash it with water and ethanol, and then dry it; (5) The graphite boat is calcined under vacuum or inert atmosphere: first, the temperature is raised to 500-1100°C at a rate of 0.3-10°C / min, and kept at this temperature for 0.5-6h; then the temperature is naturally lowered to room temperature to obtain a dust-free, acid-resistant graphite boat.
2. The method according to claim 1, characterized in that In the step (1), a CNC engraving machine is used to machine the isostatic graphite to obtain a graphite boat.
3. The method according to claim 1, characterized in that The acid in step (2) is any one of glacial acetic acid, hydrochloric acid, sulfuric acid or citric acid.
4. The method according to claim 1, characterized in that: The washing in step (4) refers to washing with water for 1 to 5 times and then washing with ethanol for 1 to 3 times.
5. The method according to claim 1, characterized in that The drying in step (4) refers to placing the cleaned graphite boat into an oven and treating it at 50-200° C. for 2-15 hours.
6. The method according to claim 1, characterized in that In step (5), the graphite boat is first moved into a high-temperature sintering furnace; then the pressure in the furnace is made to be 2×10 -7 kPa, or introduce inert gas into the furnace to make the pressure in the furnace 3 ~ 60 kPa; carry out the burning treatment under this condition.
7. The method according to claim 6, characterized in that The inert gas is nitrogen or argon.
Citation Information
Patent Citations
Graphite boat cleaning process
CN103521473A
Graphite boat cleaning process
CN106952805A
Method for modifying titanium modified expanded graphite
CN110407206A
Preparation method of coupling agent gas phase modified graphite nanosheet composite powder
CN110423494A